Efeito da ovariectomia sobre os tecidos periodontais após o reimplante dentário imediato: análise histomorfométrica, imunoistoquímica e micro-ct em ratas - Marão, Heloisa Fonseca [UNESP] (2013)
Recent researchs suggest estrogen deficiency leads to changes in periodontal tissues. In order to study dental traumatology under this condition, the aim of the study was analyze the effects of ovariectomy on periodontal tissues following immediate tooth replantation through histomorphometric, immunohistochemistry and ?-ct analysis in rats. Eighty Wistar rats (Rattus norvegicus albinos) with normal estrous cycles were randomly divided into two groups (n = 20 per group): 1) Group ovariectomized (OVX), and 2) Sham group (control group). After two months, the rats were followed by extraction of upper right incisor and immediate replantation. The rats were sacrificed immediately 28, 45 and 60 days after tooth reimplantation. Histomorphometric and immunohistochemical analysis was performed by evaluation of PCNA, OPG, CASPASE-3, RUNX-2 and TRAP proteins. Periodontal ligament was reinseted in the bone and cementum and the immunohistochemical analysis revealed PCNA expression in the periodontal ligament independent of Sham or OVX group. At 45 days, the external root resorption was greater with expression of TRAP proteins in the bone and tooth surface. However, in both groups, were also dispersed in the periodontal ligament. There was no statistically significant difference between the groups for the PCNA and TRAP proteins. The histomorphometric analysis showed statistically significant difference between groups in the histomorphological details of periodontal ligament and root resorption for the sub-items: intensity of chronic inflammatory infiltrate at 60 days (p <0.01), the organization of the periodontal ligament at 45 days (p <0:05) and depth...